2010
DOI: 10.1007/s00464-009-0794-7
|View full text |Cite|
|
Sign up to set email alerts
|

Left laparoscopic paraduodenal hernia repair

Abstract: The current data lead to the conclusion that laparoscopic paraduodenal hernia repair is a safe and feasible approach for selected patients. It can be expected that as surgeons become increasingly comfortable and facile with laparoscopic techniques, paraduodenal hernias and many other causes of acute small bowel obstruction will be increasingly managed laparoscopically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 10 publications
(3 reference statements)
0
35
0
1
Order By: Relevance
“…2,8 Peritoneal fossae develop between the 5th and 11 th gestational week due to an incomplete fusion of the posterior parietal peritoneum and the posterior abdominal wall. Superior and inferior duodenal fossae are most commonly found, in about 1-2% of cases a left paraduodenal fossa lateral to the fourth portion of the duodenum and posterior to the inferior mesenteric vein (IMV) and left colic artery is present (fossa of Landzert) 9,10 . The pathophysiology of hernia formation is not entirely clear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2,8 Peritoneal fossae develop between the 5th and 11 th gestational week due to an incomplete fusion of the posterior parietal peritoneum and the posterior abdominal wall. Superior and inferior duodenal fossae are most commonly found, in about 1-2% of cases a left paraduodenal fossa lateral to the fourth portion of the duodenum and posterior to the inferior mesenteric vein (IMV) and left colic artery is present (fossa of Landzert) 9,10 . The pathophysiology of hernia formation is not entirely clear.…”
Section: Discussionmentioning
confidence: 99%
“…Since in PDH a very proximal obstruction without extensive bowel distension is present, there is usually sufficient working space for laparoscopy. To date 15 cases of laparoscopic PDH repair have been reported in 11 publications 9 . Of these 73% were left sided and in 77% of cases the hernia was primarily closed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though all of the studies are of low LE, the potential role of laparoscopy in the diagnosis seems to be demonstrated in them and would, at times, prevent unnecessary laparotomies [298][299][300][301][302][303][304][305][306][307][308][309][310][311][312][313][314][315][316][317].…”
Section: Incarcerated/strangulated Herniasmentioning
confidence: 99%